Non-coding transcript variants of protein-coding genes – what are they good for? - Dhamija, Sonam (RNA Biol, 2018)
The total number of protein-coding genes in the human genome is not significantly higher than those in much simpler eukaryotes, despite a general increase in genome size proportionate to the organismal complexity. The large non-coding transcriptome and extensive differential splicing, are increasingly being accepted as the factors contributing to the complex mammalian physiology and architecture. Recent studies reveal additional layers of functional complexity: some long non-coding RNAs have been re-defined as micropeptide or microprotein encoding transcripts, and in turn some protein-coding RNAs are bifunctional and display also non-coding functions. Moreover, several protein-coding genes express long non-coding RNA splice-forms and generate circular RNAs in addition to their canonical mRNA transcripts, revoking the strict definition of a gene as coding or non-coding. In this mini review, we discuss the current understanding of these hybrid genes and their possible roles and relevance.